The effect of training with a multifunctional adaptive device on mastering elements performed on gymnastic rings: A comparative study of pre- and post-training routines - Eshtayev, A.; Boyboboyev, B.; Tajibayev, S.; Mamajonov, D.; Suleymanov, M.; Bekmirzayev, M. (Journal of Physical Education and Sport, 2025)
Auxiliary devices are used to enhance gymnastics training. Following the principle of training specificity, this study aimed to improve the efficiency in mastering vibration and strength training techniques on rings by incorporating a multifunctional adaptive device. The study involved 40 gymnasts - 10 pre-junior, 13 junior, and 17 senior ranging in age from 14-27 years. The control group followed a traditional training program, while the experimental group trained with a program integrating exercises using a multifunctional adaptive device developed by the researchers. The results showed a 15% improvement in general physical fitness indicators among gymnasts (p < 0.001). Specific strength qualities increased by 18%, and the total number of elements performed on the rings also increased by 18%. First-category element indicators remained unchanged, while second-category elements increased from 0.1 to 0.6 points (600% improvement). Third-category elements increased from 0.2 to 0.6 points (300% increase), and fourth-category elements increased from 0.3 to 0.5 points (67% improvement). In the pedagogical experiment, the proposed multifunctional adaptive device and the exercise complex developed from it were scientifically validated. This training approach effectively improved athletes' physical qualities and technical skills.